PELAKSANAAN KESEPAKATAN PENGELOLAAN TANAH ULAYAT ANTARA PT DUTA PALMA NUSANTARA DAN MASYARAKAT ADAT DI KABUPATEN KUANTAN SINGINGI - Muhammad Irfan Maulana; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The implementation of the customary land management agreement between PT DutaPalma and Indigenous Peoples in Kuantan Singingi Regency is regulated in an agreementagreement in 1998 which states that PT Duta Palma will build oil palm plantations with theKKPA pattern and further regulated in Law number 39 of 2014 concerning Plantations. Articles58, 59, and 60 state that palm oil companies are required to provide 20 percent of the total landarea of business use rights for facilitating the development of community gardens. However,in fact PT Duta Palma did not fulfill either an agreement with indigenous peoples or did notimplement Law Number 39 of 2014 concerning Plantations. This is due to several things,including the unavailability of land for the development of the community land in question sothat this obstacle is the strongest reason for PT Duta Palma Nusantara not to obey the servicesmade. Therefore, it is necessary to study the first stimulant, the implementation of thecustomary land management agreement between PT Duta Palma Nusantara and the IndigenousPeoples of Kuantan Singingi Regency, Second, efforts that can be made so that the customaryland management agreement between PT Duta Palma Nusantara and the Indigenous Peoplesof Kuantan Singingi Regency can be implemented.This research is a sociological legal research, because it is based on field research,namely by collecting data from interviews, questionnaires, and literature studies that have arelationship with the problem to be studied assisted by primary, secondary and tertiary data.This research uses qualitative data analysis and produces descriptive dataFrom the results of the study, it was concluded that, First, the implementation of theagreement between PT Duta Palma Nusantara and indigenous peoples in Kuantan SingingiRegency was not fully implemented. Second, the lack of communication between indigenouspeoples and pt Duta Palma Nusantara and the local government or related agencies. Third, thefuture effort is to take the non-litigation or litigation stage so that this problem finds a solutionand does not drag on. The author's suggestion is, first, to ask PT Duta Palma Nusantara withhumility to remain obedient to the agreement that has been made secondly, local indigenouspeoples continue to maintain conduciveness by taking litigation and non-litigation steps, third,if PT Duta Palma still does not fulfill the agreement then the HGU should be reviewed whereit is handed back to indigenous peoples if the land Ulayat is included in the HGU of PT DutaPalma Nusantara.Keywords: Accord – Customary Lands – Indigenous Peoples